Faktor-Faktor yang Mempengaruhi Minat Generasi Muda Bekerja Pada Perusahaan Perkebunan - Era Susanti; Mirdha Fahlevi (Jurnal Ilmiah Ekonomi Terpadu (Jimetera), 2021)
Abstract This study aims to explain the factors” that influence the interest of the younger generation to work in plantation companies. The population of this study is the entire young generation ranging from the age of 16-35 years. The sample in this study amounted to 172 respondents consisting of the younger generation with an age range of 16-35 years. The research shows that partially the independent variable, namely attitude (X1) has a positive and significant effect on the Variable Intention (Y) of the younger generation to work in plantation companies which is seen from the t- count value of 2.220 and a significant value of 0.028. Then continued with the subjective norm variable (X2) which has a positive and significant effect on the intention variable (Y) of the younger generation to work in plantation companies, which is seen from the t-count value of 2.068 and a significant value of 0.040. Behavioral control variable (X3) has a positive and significant effect on the intention variable (Y) of the younger generation to work in plantation companies, which can be seen from the "t-count value" of 6.103 and a significant value of 0.000. The feasibility analysis of the model shows the value of adjusted R2 is 0.563 which is means that the independent variable is Attitude (X1) Subjective norm (X2) and behavioral control (X3) in this study is able to explain that the influence partially or simultaneously on the dependent variable, namely Intention (Y) The younger generation working in plantation companies is 56.3% and the rest 43.7% is influenced by factors outside these variables that are not examined. Keywords: Attitude, Subjective Norm, Behavioral Control, Intention.